A STUDY ON THE SOCIAL RESPONSIBILITY OF CONSUMERS WHEN PURCHASING HOUSE HOLD ITEMS DURING LOCKDOWN PERIOD IN COIMBATORE DISTRICT - K, Dr. Anish; Sasirekha, Dr. M.N. (The journal of contemporary issues in business and government, 2021)
The aim of this research is to investigate the social responsibility of the consumers and their intentions while purchasing household items during lockdown time. The COVID-19 pandemic has forced to shut down all the regular activities and move onto online platform. But due to the lack of consumer adoption to the online grocery market, peoples were forced to purchase provisions and household items by approaching the nearest grocery shop. We conducted a survey among 532 respondents living in Coimbatore District, using google forms to study the consumers General Awareness about COVID-19, their opinion on Sense of control and also on their survival mode. Based on the analysis, findings the researcher has given relevant suggestions. The statistical tools used are Percentage Analysis, one way ANOVA, Z-Test and Chi-Square.